THE STATE OF STUDY OF THE PROBLEM OF DECISION MAKING IN SOCIO-PSYCHOLOGICAL RESEARCH (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the level of study of the problem of decision-making in socio-psychological research. The paper analyzes the scientific approaches of national scholars, researchers from the Commonwealth of Independent States, and foreign scientists who have studied the process of decision-making from different theoretical perspectives. Particular attention is paid to the psychological nature of decision-making and its cognitive, socio-psychological, and managerial dimensions. The article discusses various factors influencing the decision-making process, including individual characteristics of a person, professional experience, value orientations, motivation, and the influence of the social environment. Theoretical concepts such as H. Simon’s theory of bounded rationality, the heuristic and cognitive bias theory developed by D. Kahneman and A. Tversky, and K. Lewin’s theory of group dynamics are analyzed in order to explain the psychological mechanisms underlying decision-making processes. In addition, the role of leadership personality, managerial competencies, and socio-psychological characteristics in the development and implementation of managerial decisions is highlighted. The analysis demonstrates that the effectiveness of decision-making largely depends on psychological traits of the individual, managerial competence, the ability to adequately assess situational conditions, and the influence of social factors within organizational and group contexts